Uji Coba Lapangan Terkait Nasehat Perjalanan (WHO) dalam Travelling selama Pandemi Covid-19 - Sarah Geltri Harahap; Paramita Boni Lestari; Irmawati Apriany Thobias; Yania Febsi; Hadi Pratomo (Syntax Corporation Indonesia, 2021)
WHO determines the Covid-19 pandemic status followed by various advice in order to reduce the spread of the virus, one of which is related to traveling. Indonesia currently has no specific travel advice that has been prepared to meet the needs of the community in traveling during the Covid-19 pandemic. Therefore, travel advice is needed which refers to travel advice made by WHO that is adjusted to the perception of the people in Indonesia. Objective: To assess how the public perception (informant) of the travel advice video issued by WHO to reduce the spread of Covid-19 during the trip. Method: This research is a qualitative descriptive study of people's perceptions of video travel advice as a guide for traveling during the COVID-19 pandemic for triangulation of data and in-depth analysis. The variable used is using pretest theory. Research Results: There are variations of answers and opinions from informants on the Q and A videos. Overall found opinions that say that the video is quite interesting and can provide information that helps people who want to travel or travel. Conclusion: Based on the perceptions conveyed by the information in this study, in general the Q and A videos recommended by WHO can be applied in Indonesia, by adjusting to the development of the disease and the current situation in Indonesia